Pemanfaatan casa dalam observasi motilitas spermatozoa semen cair Sapi Madura dalam pengencer berbeda (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
The purpose of this study was to measure the motility of Madura bullspermatozoa using three different diluents (tris aminomethane, CEP-2 andskim milk) duringcold storage. The research material used were 2 Madurabulls. Collecting semen method used artificial vagina, followed by freshsemen analysis and processing of liquid semen. Observation of liquid semenquality was carried out up to the 5th days of cold storage. Motilityexamination of semen liquid used Computerized Assisted Semen Analysis(CASA), namely SCA v.5.2. The parameters measured were: progressive motility,motility, velocity straight linear (VSL), velocity curve linear (VCL),velocity average pathway (VAP), straightness (STR), linearity (LIN), wobble(WOB), hyperactivity (H), Beat cross frequency (BCF), amplitude lateral head(ALH). Data was analyzed by Minitab 17. Motility and progressive motility ofspermatozoa in tris aminomethane and CEP-2 were higher than skim milk for 5days of cold storage. The VCL value of tris aminomethane was higher thanCEP-2 and skim milk. VSL scores barely show the difference among diluents.VAP values in tris aminomethaneand CEP-2 are higher than skim milk at thebeginning of storage. The LIN, STR and WOB values of the CEP-2 and skim milkyield higher values than tris aminomethane. The percentage value ofhyperactivity spermatozoa was same among diluents. The ALH value oftrisaminomethane was higher than CEP-2 and skim milk. BCF values in CEP-2was higher than skim milk and tris aminomethane. Tris aminomethane and CEP-2can support the motility of Madura bull spermatozoa than skim milkfor 5 daysof storage